ApoC-III Glycoforms Are Differentially Cleared by Hepatic TRL (Triglyceride-Rich Lipoprotein) Receptors. Issue 10 (October 2019) - Kegulian, Natalie C.; Ramms, Bastian; Horton, Steven; Trenchevska, Olgica; Nedelkov, Dobrin; Graham, Mark J.; Lee, Richard G.; Esko, Jeffrey D.; Yassine, Hussein N.; Gordts, Philip L.S.M.
Abstract : Objective: ApoC-III (apolipoprotein C-III) glycosylation can predict cardiovascular disease risk. Higher abundance of disialylated (apoC-III2 ) over monosialylated (apoC-III1 ) glycoforms is associated with lower plasma triglyceride levels. Yet, it remains unclear whether apoC-III glycosylation impacts TRL (triglyceride-rich lipoprotein) clearance and whether apoC-III antisense therapy (volanesorsen) affects distribution of apoC-III glycoforms. Approach and Results: To measure the abundance of human apoC-III glycoforms in plasma over time, human TRLs were injected into wild-type mice and mice lacking hepatic TRL clearance receptors, namely HSPGs (heparan sulfate proteoglycans) or both LDLR (low-density lipoprotein receptor) and LRP1 (LDLR-related protein 1). ApoC-III was more rapidly cleared in the absence of HSPG (t1/2 =25.4 minutes) than in wild-type animals (t1/2 =55.1 minutes). In contrast, deficiency of LDLR and LRP1 (t1/2 =56.1 minutes) did not affect clearance of apoC-III. After injection, a significant increase in the relative abundance of apoC-III2 was observed in HSPG-deficient mice, whereas the opposite was observed in mice lacking LDLR and LRP1. In patients, abundance of plasma apoC-III glycoforms was assessed after placebo or volanesorsen administration. Volanesorsen treatment correlated with a statistically significant 1.4-fold increase in the relative abundance of apoC-III2 and a 15% decrease in that of apoC-III1 . The decrease in relative apoC-III1 abundance was strongly correlated with decreased plasma triglyceride levels in patients. Conclusions: Our results indicate that HSPGs preferentially clear apoC-III2 . In contrast, apoC-III1 is more effectively cleared by LDLR/LRP1. Clinically, the increase in the apoC-III2 /apoC-III1 ratio on antisense lowering of apoC-III might reflect faster clearance of apoC-III1 because this metabolic shift associates with improved triglyceride levels. Abstract : Supplemental Digital Content is available in the text.